Students’ Opinion on English Group Discussion to Improve Collaboration Skill - Prayudha.S, Joko (English Language Education, Universitas Internasional Batam, 2023)
Collaboration skills are one of the skills that are emphasized in 21st century learning where students are asked to be able to cooperate well in facing and overcoming problems that arise in learning, including when learning English. Collaboration skills in learning English enable students to be able to work together in helping and overcoming problems encountered when learning English. Therefore, this study aims to find out students' opinions on English group discussions to improve collaboration skills in learning English. The method used in this research is to use qualitative through a descriptive approach. The sample used in this study consisted of 36 students who were learning English. Data was collected through observation and interviews to determine students' perceptions of the English group discussion method in improving collaboration skills. After the data is collected, the data is analyzed through three stages, namely data reduction, data display and data conclusion. The results showed that some students had a good and positive interest in increasing collaboration skills using the English group discussion method. In fact, students tend to be able to do their best in doing English assignments by collaborating and studying together so that there is an increase in English achievement.